Econometric analysis of monetary transmission channels in Croatia - Vizek, Maruška (Array, 2008)
Abstract: The aim of this paper is to explore the characteristics and functioning of monetary transmission in Croatia. Time series analysis (unit root test, VAR, Johansen cointegration procedure, Granger causality tests and error correction model) is used to estimate the influence of exchange rate, interest rate and narrow money on the real economic activity.The results of econometric analysis suggest that monetary policy in Croatia had a significant influence on the real activity through the direct monetary transmission and exchange rate channel.Furthermore, the results of statistical tests suggest that the interest rate channel is not active.The short-run interest rate inelasticity of Croatian economy combined with a strong exchange rate channel could present a great difficulty once Croatia joins the EMU, since the interest rate channel is the most important channel of monetary transmission in the EU, while the exchange rate channel will be eliminated upon adopting the euro. This could provoke a non-responsiveness of the Croatian economy to the EU monetary policy or it could make the monetary transmission asymmetric. However, high euroisation of the Croatian economy could facilitate the interest rate transmission once the euro is adopted